Sleep duration and self-rated health: the national health interview survey 2008 - Shankar, Anoop; Charumathi, Sabanayagam; Kalidindi, Sita (Sleep (New York, N.Y.), 2011)
Self-rated health (SRH) has been shown to consistently predict overall mortality and cardiovascular mortality in several population-based studies across the world. Similarly sleep duration have been found to be associated with cardiovascular disease (CVD) and mortality. However, relatively few studies have examined the association between sleep duration and SRH, and the results have not been consistent. We conducted a cross-sectional study of n = 20,663 National Health Interview Survey 2008 participants ≥ 18 years of age (56.2% women). Sleep duration was categorized as ≤ 5 h, 6 h, 7 h, 8 h, and ≥ 9 h. The main outcome interest was fair/poor SRH (n = 3043). We found both short and long sleep duration to be independently associated with fair/poor SRH, independent of age, sex, race-ethnicity, smoking, alcohol intake, body mass index, physical activity, depression, diabetes mellitus, hypertension, and CVD. Compared with a sleep duration of 7 h (referent), the multivariate odds ratio (95% confidence interval) of fair/poor SRH was 2.29 (1.86-2.83), 1.68 (1.42-2.00), 1.38 (1.18-1.61), and 1.98 (1.63-2.40) for sleep duration ≤ 5, 6, 8, and ≥ 9 h. This association persisted in subgroup analyses by gender, race-ethnicity, and body mass index categories. Compared with sleep duration of 7 h, there was a positive association between both shorter and longer sleep duration and fair/poor self-rated health in a representative sample of US adults.